1989
DOI: 10.1007/bf02653291
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐liquid and solid‐liquid mass transfer in three‐phase sparged reactors with and without ultrasound

Abstract: Gas‐liquid and solid‐liquid mass transfer in three‐phase sparged reactor has been studied with and without super‐imposed ultrasound. The results show marginal enhancement in mass transfer coefficient due to ultrasound. Thus it has been concluded that the reported enhancement in the rates of heterogeneous reactions due to ultrasound is likely due to other, e.g., chemical, effects of ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Using a three-phase sparger reactor, the effects of ultrasound were investigated for a solid-liquid and a gas-liquid reaction (Jadhav and Pangarkar, 1989). The authors concluded that ultrasound had a greater effect on the solid-liquid reaction but that the enhancement in the mass-transfer coefficient was not very significant.…”
Section: Mass-transfer Studiesmentioning
confidence: 99%
“…Using a three-phase sparger reactor, the effects of ultrasound were investigated for a solid-liquid and a gas-liquid reaction (Jadhav and Pangarkar, 1989). The authors concluded that ultrasound had a greater effect on the solid-liquid reaction but that the enhancement in the mass-transfer coefficient was not very significant.…”
Section: Mass-transfer Studiesmentioning
confidence: 99%
“…There is a need to improve our understanding of the extent of mass transfer and reaction intensification resulting from ultrasonic irradiation as a function of process and operating parameters in heterogeneous gas-liquid, liquid-liquid, and gas-liquid-solid systems. [32][33][34] Shojaie et al 35 presented experimental results on the sonication of SO 2 and NO species in water and NaOH solutions at 20 kHz in the presence of argon and suggested that the yields of H 2 -SO 4 , nitrous acid (HNO 2 ), and HNO 3 resulted from interactions with H 2 O 2 generated from water during the adiabatic collapse of the microbubbles in solution since the formation rate of H 2 O 2 limited the yields of oxidation products. However, to the best of our knowledge, no study has yet looked into the possibility of developing an advanced sonochemical aqueous scrubber of any kind in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…The collapse of these bubbles leads to local transient high temperatures (≥5000 K) and pressures (≥1000 atm), resulting in the generation of highly reactive species including hydroxyl (•OH), hydrogen (H•), and hydroperoxyl (HO 2 • ) radicals and hydrogen peroxide. A number of studies have demonstrated the effectiveness of ultrasound for the oxidation of organics, destruction of pathogenic organisms, and treatment of water and wastewater either as a sole means of treatment or in combination with other oxidation processes such as ozonation, UV irradiation, and photocatalysis. Despite recent advances in homogeneous sonochemistry, the mechanisms of heterogeneous sonochemistry remain poorly understood. There is a need to improve our understanding of the extent of mass transfer and reaction intensification resulting from ultrasonic irradiation as a function of process and operating parameters in heterogeneous gas−liquid, liquid−liquid, and gas−liquid−solid systems. Shojaie et al presented experimental results on the sonication of SO 2 and NO species in water and NaOH solutions at 20 kHz in the presence of argon and suggested that the yields of H 2 SO 4 , nitrous acid (HNO 2 ), and HNO 3 resulted from interactions with H 2 O 2 generated from water during the adiabatic collapse of the microbubbles in solution since the formation rate of H 2 O 2 limited the yields of oxidation products. However, to the best of our knowledge, no study has yet looked into the possibility of developing an advanced sonochemical aqueous scrubber of any kind in the open literature.…”
Section: Introductionmentioning
confidence: 99%